Lexical bundles in L2 English academic texts: Relationships with holistic assessments of writing quality. (November 2022) - Appel, Randy
Abstract: Appropriate use of frequently occurring multiword sequences is now seen as an important part of linguistic proficiency in spoken and written discourse (e.g., Biber et al., 1999; Wray, 2002) yet how these structures are used by second language (L2) English learners remains insufficiently understood. This study investigates how L2 English learners make use of these structures in their academic English writing. Data was collected from a first-year academic English writing program at the university level in Japan. To control for topic and condition influences, all texts were written in response to a common prompt and composed as part of normal classroom assessment. These essays were graded by trained professionals using a standardized rubric. Subsequently, the evaluated writing was separated into lower-level (n = 250) and higher-level (n = 247) corpora before being analyzed for the presence of 3-7-word lexical bundles. Qualitative and quantitative measures were then used to identify inter-group differences. While functional classifications revealed only minor differences between writer groups, quantitative analyses uncovered several key differences. Methodological and pedagogical implications are discussed.